PEDRO DE GUEVARA AND TRANSITIONAL FORTIFICATION. THE PLAN FOR THE REFORM OF THE DEFENSES OF VALENCIA, 1544 - Santiago Lillo Giner; Jorge Llopis Verdú (EGA, 2012)
In 1544 Pedro de Guevara executed his plan to reform the defenses of Valencia. This is the first “reliable” cartographic representation of the city and constitutes a paradigmatic example of the so-called Transitional Fortification, but also involves the introduction of the new renaissance way of representing the city, in which the image acquires a strong will to objectivity, clearly different from the idealized graphical view of previous centuries.